Toward a feminist agroecology: achieving a socially just and sustainable food systems transformation - Zaremba, Haley; Elias, Marlène; Rietveld, Anne; Bergamini, Nadia (2022)
Food systems must be transformed if we are to feed the world without destroying the planet. Agroecological principles are central to creating and sustaining that change, but their transformative potential must be strengthened by better integrating critical gender and social inclusion considerations into agroecological approaches. In order for agroecology to achieve its espoused twin aims of social and ecological wellbeing, women and other historically marginalized stakeholders must be empowered and centered as the movement’s protagonists. Based on the article ‘Toward a Feminist Agroecology’1, this brief outlines key gender issues that must be addressed to achieve an equitable and sustainable agroecological transition.